Working Memory And Activities Of Daily Living Among Children With Intellectual Disability. - Bhati, Lokesh; Sharma, Hariom (Journal of Namibian Studies)
Intelligence is an ability to learn from experience, adapt to new situations, understand abstract concepts and adapt to new situations. This study attempts to show the correlation between working memory and activities of daily living among children with intellectual disability. Working memory is used to hold information temporarily during performing cognitive tasks like learning, comprehension, reasoning, and problem-solving. The required daily tasks that a person must carry out in order to survive are included in the category of activities of daily living. The majority of healthy adults can carry out these self-care tasks on their own and without much support. Throughout childhood and the early years of adulthood, these basic activities (eating, toileting, dressing, etc.) are acquired gradually. When a child is intellectually disabled, their level of cognitive functioning is considered to be impaired. It denotes a condition in which cognitive development of children is seriously hindered, making it problematic for child to comprehend successfully, to solve problems and adjust in environment. Digit Span Test given by Dr. A.J. Malin (2003) is used to measure working memory and Waisman ADL checklist given by Waisman (2013) is used to measure activities of daily living of children with intellectual disability. The sample size taken for the present study is 50 and the participants belong to age range of 11 to 16 years old. Fifty children with moderate intellectual disability attending the special school of Delhi NCR region are included in the study. Both the tools are used to study working memory and activities of daily living among children with intellectual disability. The hypothesis formulated for the present study states that there will be significant correlation between working memory and activities of daily living among children with intellectual disability. The findings of the study reveal there is a meaningful corelation between working memory and activities of daily living among children with intellectual disability.